Analyze the conceptual understanding of earthquakes among geography teachers in Ranau, Sabah - Soon Singh Bikar Singh; Zulfikar Rabe; Balan Rathakrishnan (Review of International Geographical Education Online (RIGEO), 2021)
The Sabah Meteorological Department (2015) reports that in the next 20 years a large scale earthquake will hit Sabah. This inevitability means that the local community needs to be sufficiently informed so as to be prepared for disaster. Formal education can be used as a medium for conveying knowledge about earthquakes. However, scholars believe that to impart such knowledge, teachers' understanding of earthquake concepts needs to be evaluated as they are the main sources of information on the topic. This study applied a concurrent triangulation mixed method model to explore the understanding of earthquake concepts among Geography teachers in Ranau. The quantitative data were collected through a survey, while the qualitative data were collected through teachers' interviews. Random sampling methods were used to select 80 Geography teachers from nine secondary schools in Ranau, Sabah. Of these, 18 were selected through the purposive sampling method for interviews. Triangulation of quantitative and qualitative data revealed that the level of understanding of the earthquake concept and the level of readiness for an earthquake disaster is moderate. The findings also indicated that female teachers are more aware of the concept of earthquakes and male teachers are more prepared for them due to physical and emotional factors. Furthermore, senior teachers are more aware of the concepts and are more prepared for the earthquake than their junior colleagues. Finally, the findings of this study contribute to the science of earthquake education in Malaysia and aid Geography teachers, as well as assisting schools to help teachers improve their under standing of earthquake concepts.